2001
DOI: 10.1086/318541
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin‐18, a Th1 Cytokine, in Human Gastric Mucosa Is Increased inHelicobacter pyloriInfection

Abstract: Interleukin-18 (IL-18), a cytokine that promotes Th1 responses, is processed to the active mature protein by caspase-1. The effects of Helicobacter pylori infection on gastric IL-18 and caspase-1 were examined. In antral mucosa, IL-18 mRNA expression was greater (P<.01) in H. pylori-positive (n=40) than in H. pylori-negative patients (n=29) with normal mucosa. Inactive precursor (24 kDa) and mature (18 kDa) IL-18 were present in antral biopsy specimens from uninfected and infected subjects. In corpus mucosa, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 52 publications
7
61
1
3
Order By: Relevance
“…An increased IL-18 expression has been reported in human atherosclerotic plaques 100) , and animal models further support the proatherogenic role of IL-18 101) and beneficial effects of IL-18 inhibition on plaque progression and composition 102) . In particular, several epidemiologic studies have reported that H. pylori infection upregulates IL-18 production from human gastric epithelial cells and lamina propria mononuclear cells isolated from H. pylori-infected gastric mucosa [103][104][105] . Furthermore, the serum H. pylori-IgG level is positively correlated with the serum IL-18 level 81) , and the IL-18 level is influenced by CagA-positive H. pylori strains 106) .…”
Section: H Pylori and Endothelial Dysfunctionmentioning
confidence: 99%
“…An increased IL-18 expression has been reported in human atherosclerotic plaques 100) , and animal models further support the proatherogenic role of IL-18 101) and beneficial effects of IL-18 inhibition on plaque progression and composition 102) . In particular, several epidemiologic studies have reported that H. pylori infection upregulates IL-18 production from human gastric epithelial cells and lamina propria mononuclear cells isolated from H. pylori-infected gastric mucosa [103][104][105] . Furthermore, the serum H. pylori-IgG level is positively correlated with the serum IL-18 level 81) , and the IL-18 level is influenced by CagA-positive H. pylori strains 106) .…”
Section: H Pylori and Endothelial Dysfunctionmentioning
confidence: 99%
“…Previous studies have shown that IL-18 is increased in different inflammatory conditions, such as Crohn's disease (37,38), rheumatoid arthritis (39), and leprosy (40). In Helicobacter-infected individuals, IL-18 mRNA expression was increased in the gastric mucosa (41,42). The serum IL-18 level was significantly increased in patients with gastric carcinoma, which is frequently found to be associated with H. pylori infection (2,43).…”
Section: Vaccine-induced Immunity Against Helicobacter Pylorimentioning
confidence: 99%
“…Tomita et al (15) reported that antral IL-18 mRNA levels were up-regulated in H. pylori infection, whereas mature IL-18 protein was present in mucosa of both infected and uninfected subjects as measured by immunoblot analyses. In contrast, Fera et al reported that antral H. pylori infection was associated with IL-18 production as determined by immunohistochemistry; whereas IL-18 mRNA was expressed irrespective of H. pylori infection (16).…”
Section: T Hementioning
confidence: 99%
“…pylori strains containing an intact cag pathogenicity island (PAI) 4 , which encodes the type IV secretion system, and the outer inflammatory protein (OipA), which encodes the outer membrane protein, have been reported to increase the risk of more severe clinical outcomes (17,18). Tomita et al (15) reported that antral IL-18 mRNA levels were independent of the presence or absence of the cag PAI; however the relationship between OipA and IL-18 is not understood.…”
Section: T Hementioning
confidence: 99%